Paracoccidioidomycosis differential diagnosis: case series - Martins, Ezequias Batista; Silva, Natalia Chilinque Zambão; Ferreira, Laura da Cunha; Ronchini, Karla Regina Oliveira de Moura; Caetano, Daniel Abner Paiva; Vilte, Remberto Mauricio de la Cruz Vargas; Martins, Ianick Souto; Costa, Anielle de Pina; McBenedict, Billy; Santos, Juliana Arcenio Alves; Machado, Carolina Romero; Souza, Danyelle Cristina; et al. (Brazilian Journal of Case Reports, 2023)
Paracoccidioidomycosis is a neglected disease and the most important systemic mycosis in Latin America. This fungal infection is directly linked to activities related to the rural environment, such as agriculture. Despite being a frequently diagnosed disease in Brazil, the real rates of prevalence and incidence are not estimated due to the non-mandatory notification of the disease, which was recently implemented in 2020. We report three interesting cases of Paracoccidioidomycosis in immunocompetent adults, with varied clinical manifestations.